Arge quidia Smith, 1989 (Hymenoptera: Argidae) at Ramsar site, Panama bay wetland - Santos-Murgas, Alonso (2023)
In the present work, the species Arge quidia Smith, 1989 (Hymenoptera: Symphyta: Argidae) associated with Coccoloba caracasana Meisn, 1856 (Plantae: Polygonaceae) is recorded in the RAMSAR Wildlife Refuge Protected Area, Bahía de Panamá Wetland. Biological and ecological data of A. quidia are provided.